Novel Catalysts in Advanced Oxidation of Organic Pollutants - Atalay, Süheyda; Ersöz, Gülin (SpringerBriefs in Green Chemistry for Sustainability, 2016)
This brief summarizes the role of certain catalysts and associated processes that are involved in the reduction or elimination of hazardous substances from wastewater and the exploitation of renewable raw materials. The authors begin by providing a summary of the most recent developments in catalysts used in the advanced oxidation of organic pollutants in aqueous phase. Advanced Oxidation Processes (AOPS) are described in terms of homogeneous and heterogeneous catalysts. Some emphasis is placed on the role nanocatalysts, perovskite-type catalysts, and green catalysts play in several AOPs such as Fenton Chemistry, photocatalytic oxidation, and the hybrid technologies that combine different processes. Catalyst preparation, characterization, reaction chemistry, and process technology are described. Specific wastewater case studies which illustrate the role of these catalysts in AOPs completes the brief.